Pura Ulun Danu Beratan Sebagai Daya Tarik Wisata (DTW) Desa Candikuning Kabupaten Tabanan - Gede Mahardika (Jayapangus Press, 2021)
Ulun Danu Beratan Temple, which is unique because one part of the temple is in the middle of Lake Beratan, gives its own charm for tourists. The lake is actually very sacred by the Balinese because it is considered a source of prosperity in life. Ulun Danu Beratan Temple and Beratan Lake are not spared from tourism activities, even the charm of these two tourist attractions seems to attract the interest and attention of local, domestic and foreign tourists. The formulation of the problem in this study is Why Ulun Danu Temple is used as a Tourist Attraction?. The specific purpose of this research is to describe Ulun Danu Temple as a cultural tourism attraction. To analyze the formulation of the research problem using Structural Functionalism Theory. Data obtained by observation, interview and documentation techniques. The results of this study are as follows: (1) The cultural form that is owned by the Ulun Danu Beratan tourist attraction is the beauty of the Ulun Danu Beratan Temple which is very fascinating from the royal heritage of Mengwi I Gusti Agung Putu in the year Saka 1556 based on the estimates described in the Mengwi chronicle. (2) The attraction of natural beauty offered by the Ulun Danu Beratan Temple attraction offers the beauty of the lake, the natural beauty of the hills and the cool air that can be enjoyed by every tourist. The conclusions in this study are Ulun Danu Temple as a cultural and natural tourist attraction.